Handbook for paints and protective coatings for facilities. (U.S. Dept. of Defense : [Distributed by DODSSP], 1995)
This handbook is provided as guidance for Department of Defense personnel wishing to apply architectural paints or protective coatings to military structures fixed in place. It contains information on the composition of coatings, their mechanisms of curing, selection for different substrates and structures, application, inspection, and failure analysis.
Supercedes NAVFAC MO-110, June 1981.
Keywords: Paint -- Handbooks, manuals, etc.; Protective coatings -- Handbooks, manuals, etc.; elektronické knihy; electronic books